Teacher’s Strategies in Teaching Receptive English Skills to Students at Secondary School - Bowu, Nella Aswi; Dollah, Syarifuddin; Salija, Kisman (Celebes Journal of Language Studies, 2023)
The objectives of the research are to find out the strategies the teacher used in teaching receptive English skills, the constraints faced by the teacher in teaching receptive English skills, and how students' engagement in teaching receptive English skills using teacher's strategies. This research the researcher used a descriptive qualitative research design to find out the teacher's strategy in teaching Receptive English skills at secondary school. The subjects of this research consisted of 1 English teacher and the students of TKJ 4 class at SMK Telkom Makassar. By applying classroom observations and interviews, the researcher found the results of this research. The results of the research are: (1) the strategies that teacher used in teaching Receptive English skills which are brainstorming, sentence completion, summarizing, the use of technology, previewing, retelling, and group discussion. (2) The constraints that teacher faced in the classroom are the level of difficulty, students' lack of vocabulary, and students' concentration. (3) The majority of the students give a positive response to the teaching strategies used by the teacher in teaching receptive English skills.